DAMAGE IN HISTORIC RAMMED EARTH STRUCTURES: A CASE STUDY AT AMBEL, ZARAGOZA, SPAIN - Jaquin, Paul; Gerrard, Christopher; Augarde, Charles; Canivell, Jacinto (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
This paper examines the possible causes of damage to historic rammed earth structures based on a case study of a medieval and later building, formerly a preceptory of the Military Orders, in the village of Ambel in Aragon, north-east Spain. Structural and water-based mechanisms of damage are reviewed and an engineering basis for the cause of damage is proposed. Since a number of repair strategies have already been attempted on this structure, their effectiveness is also discussed. A four storey granary at the north-east corner of the preceptory complex is described in detail since it encapsulates many damage mechanisms and repair strategies which are common to historic rammed earth. The granary tower has a random rubble foundation, which is probably in part the remains of previous building, with rammed earth walls for the three storeys above. This rammed earth was originally rendered and scored to imitate fired brick but almost all of this has now fallen away. The gable end of the building has fired brick quoins, and now leans outwards slightly at the head of the wall. There is evidence of water damage because the building was neglected in the past, though not enough to initiate collapse. Structural and water based damage mechanisms are identified, and example repair strategies used at Ambel are described.